Contrasting He-C relationships in Nicaragua and Costa Rica: insights into C cycling through subduction zones - Shaw, A. M.; Hilton, D. R.; Fischer, T. P.; Walker, J. A.; Alvarado, G. E. (Earth and Planetary Science Letters, 2003)
We report He-3/He-4 ratios, relative He, Ne, and CO2 abundances as well as delta(13)C values for volatiles from the volcanic output along the Costa Rica and Nicaragua segments of the Central American arc utilising fumaroles, geothermal wells, water springs and bubbling hot springs. CO2/He-3 ratios are relatively constant throughout Costa Rica (av. 2.1 X 10(10)) and Nicaragua (av. 2.5 X 10(10)) and similar to arcs worldwide (similar to1.5 X 10(10)). delta(13)C values range from -6.8parts per thousand (MORB-like) to -0.1parts per thousand (similar to marine carbonate (0parts per thousand)). He-3/He-4 ratios are essentially MORB-like (8 +/- R-A) with some samples showing evidence of crustal He additions - water spring samples are particularly susceptible to modification. The He-CO2 relationships are consistent with an enhanced input of slab-derived C to magma sources in Nicaragua ((L+S)/M = 16; where L, M and S represent the fraction of CO2 derived from limestone and/or marine carbonate (L), the mantle (M) and sedimentary organic C (S) sources) relative to Costa Rica ((L+S)/M = 10). This is consistent with prior studies showing a higher sedimentary flux to the arc volcanics in Nicaragua (as traced by Ba/La, Be-10 and La/Yb). Possible explanations include: (1) offscraping of the uppermost sediments in the Costa Rica forearc, and (2) a cooler thermal regime in the Nicaragua subduction zone, preserving a higher proportion of melt-inducing fluids to subarc depths, leading to a higher degree of sediment transfer to the subarc mantle. The absolute flux Of CO2 from the Central American arc as determined by correlation spectrometry methods (5.8 X 10(10) mol/yr) and CO2/He-3 ratios (7.1 X 10(10) mol/yr) represents approximately 14-18% of the amount of CO2 input at the trench from the various slab contributors (carbonate sediments, organic C, and altered oceanic crust). Although the absolute flux is comparable to other arcs, the efficiency Of CO2 recycling through the Central American are is surprisingly low (14-18% vs. a global average of similar to50%). This may be attributed to either significant C loss in the forearc region, or incomplete decarbonation of carbonate sediments at subarc depths. The implication of the latter case is that a large fraction of C (up to 86%) may be transferred to the deep mantle (depths beyond the source of arc magmas). (C) 2003 Elsevier B.V. All rights reserved.
725paTimes Cited:98Cited References Count:50